The power of stories to connect with customers : digital storytelling as a communication marketing tool to engage with Millennials and its impact on the creation of value for firms - Fernandes, Mariana Santos de Matos Ramirez (2019)
Nowadays, engaging with customers is a major challenge for any business. Millennials are known for their distinctive attitude towards brands, having proved to be an attractive target for many consumer industries, however, engaging with them is not an easy task, as they are more demanding towards brands than any other generation. The main purpose of this dissertation is to understand if digital storytelling is an effective communication marketing tool for engaging with Millennials, and analyze its impact on the creation of value for firms. In order to respond to the main research questions of this study, an online survey was conducted among Millennials, exposing them to two YouTube ads, with straight-sell and storytelling execution styles, in order to study the effectiveness of the communication in creating engagement among Millennials, and its impact on the creation of added value for firms, depending on the ad type. Results show the superiority of the storytelling ad for engaging with Millennials across several customer reactions: trust, commitment, emotional brand attachment, involvement, as well as positive word of mouth and feedback provided to the brand. Satisfaction, purchase intention and referral behavior, did not differ significantly between the two ad execution styles. Additional findings reveal that a digital storytelling ad produces a higher level of engagement among Millennials, contributing more for the generation of added value for firms, while compared to a straight-sell execution style ad. As a suggestion, marketeers should consider adopting this strategy for developing strong and long-lasting relationships with Millennials.